Peran Guru PKN dalam Pembentukan Karakter Warga Negara - ., Mariyani (Literasi: Jurnal Ilmu Pendidikan, 2018)
Character building efforts through education in Indonesia can be said to have not been implemented optimally. It is illustrated by the many behaviors of learners that lead to immoral behavior and contrary to the values   of Pancasila. The moral crisis must be addressed immediatelyby increasing efforts to shape the character of good citizens. Character building through education is charged to every subject at school. One of the subjects charged in shaping the character of good citizens is through Civics subjects. The subject of Civics becomes a very effective approach in achieving the goal of character formation. This paper seeks to describe how the role of Civics teacher as a central ï¬ gure in shaping the character of learners in accordance with the expected goals. The method used in this paper is a literature review of ideas that strengthen this paper. Teachers become central ï¬gures in the learning process so that the role of teachers is very large in shaping the character of learners in accordance with the value of Pancasila. Teachers must change the paradigm that teachersonly as teachers become educators. That’s because teachers in shaping characters are not through knowledge transfer but are able to bring students in real experience through learning. The role of Civics teachers in forming the character of citizens include 1) the role of teachers as teachers in understanding the values   of characters to be developed; 2) the role of teachers as the compilers of character-based learning devices; 3) the role of teachers as implementers of innovative learning and 4) the role of teachers as role models in character building.Keywords: role of teacher, Civics and character education